Exploring the Role of Low-Density Neutrophils During Mycobacterium tuberculosis Infection - Rankin, Ananda N.; Hendrix, Skyler V.; Naik, Sumanta K.; Stallings, Christina L. (Frontiers in Cellular and Infection Microbiology, 2022)
Tuberculosis (TB) is caused by infection with the bacterium Mycobacterium tuberculosis (Mtb), which primarily infects the lungs but can also cause extrapulmonary disease. Both the disease outcome and the pathology of TB are driven by the immune response mounted by the host. Infection with Mtb elicits inflammatory host responses that are necessary to control infection, but can also cause extensive tissue damage when in excess, and thus must be precisely balanced. In particular, excessive recruitment of neutrophils to the site of infection has been associated with poor control of Mtb infection, prompting investigations into the roles of neutrophils in TB disease outcomes. Recent studies have revealed that neutrophils can be divided into subpopulations that are differentially abundant in TB disease states, highlighting the potential complexities in determining the roles of neutrophils in Mtb infection. Specifically, neutrophils can be separated into normal (NDN) and low-density neutrophils (LDNs) based on their separation during density gradient centrifugation and surface marker expression. LDNs are present in higher numbers during active TB disease and increase in frequency with disease progression, although their direct contribution to TB is still unknown. In addition, the abundance of LDNs has also been associated with the severity of other lung infections, including COVID-19. In this review, we discuss recent findings regarding the roles of LDNs during lung inflammation, emphasizing their association with TB disease outcomes. This review highlights the importance of future investigations into the relationship between neutrophil diversity and TB disease severity.